Orthodontic treatment for a patient with multiple sclerosis - Manal A Bakathir (Wolters Kluwer Medknow Publications, 2017)
Multiple sclerosis (MS) is a chronic, autoimmune inflammatory disorder of the central nervous system (CNS) that affects myelinated axons, destroying the myelin and damaging axons to varying degrees. The course of MS is highly varied and unpredictable. Metals used during orthodontic treatment can negatively affect imaging techniques used to diagnose and monitor the progression of MS, while medications used to treat MS can negatively affect orthodontic tooth movement. The present case report highlights some of the challenges encountered during orthodontic treatment of a patient with MS and how to overcome them. The patient was a 20-year-old woman with complaints of diastema and spacing in the upper arch. Although closing the spaces was challenging due to some of the MS medications, she was treated successfully, without complications, within 20 months using closing loops.